2020
DOI: 10.1108/rpj-12-2018-0314
|View full text |Cite
|
Sign up to set email alerts
|

Improving the forming quality of fused filament fabrication parts by applied vibration

Abstract: Purpose The purpose of this study is to investigate the efficiency of applied vibration in improving the forming quality (mechanical property and dynamics characteristics) of fused filament fabrication (FFF) parts. Design/methodology/approach A vibrating FFF three-dimensional printer was set up, with which the samples fabricated in different directions were manufactured separately without and with vibration applied. A series of experimental tests, including tensile tests, dynamics tests and scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…It is also reported from this study that the use of a vibrating nozzle could also slightly increase the elastic modulus of the printed material from 2.5 ± 0.1 GPa to 2.7 ± 0.1 GPa [76]. Similarly, Jiang et al reported an increased tensile strength of PLA of 50% once this material was printed along a z orientation using a vibrating nozzle [77].…”
Section: Vibration-assisted Fff (Va-fff) Methodssupporting
confidence: 75%
“…It is also reported from this study that the use of a vibrating nozzle could also slightly increase the elastic modulus of the printed material from 2.5 ± 0.1 GPa to 2.7 ± 0.1 GPa [76]. Similarly, Jiang et al reported an increased tensile strength of PLA of 50% once this material was printed along a z orientation using a vibrating nozzle [77].…”
Section: Vibration-assisted Fff (Va-fff) Methodssupporting
confidence: 75%
“…The finite element analysis showed that the SR was obviously reduced. Jiang et al 15 found that using vibration machining could enhance the ME parts' forming quality (both mechanical and dynamic properties), but the impact on the surface quality was not taken into consideration. Wang et al 16 performed SR tests on ME parts in different printing directions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, applying vibration into the process of ME has a great potential to improve the MFB, and thereby enhance the forming quality of ME parts. However, few scholars have proposed this concept at present [22,23], and little corresponding information (either theoretical or experimental data) is available. To cover this gap, this paper establishes a dynamic model of the MFB (DMMFB) to analyze the pressure drop, shear stress and apparent viscosity in the ME liquefier without and with different vibrations applied.…”
Section: Introductionmentioning
confidence: 99%